2007
DOI: 10.1007/s10472-007-9083-0
|View full text |Cite
|
Sign up to set email alerts
|

A new modal logic for reasoning about space: spatial propositional neighborhood logic

Abstract: It is widely accepted that spatial reasoning plays a central role in artificial intelligence, for it has a wide variety of potential applications, e.g., in robotics, geographical information systems, and medical analysis and diagnosis. While spatial reasoning has been extensively studied at the algebraic level, modal logics for spatial reasoning have received less attention in the literature. In this paper we propose a new modal logic, called Spatial Propositional Neighborhood Logic (SpPNL for short) for spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…While the satisfiability problem for spatial modal logics with projection modalities turns out to be highly undecidable [7,9], we prove that Cone Logic enjoys a decidable satisfiability problem (in fact, PSPACE-complete) by taking advantage of a suitable filtration technique. We also show that Cone Logic subsumes interesting interval temporal logics such as the temporal logic of subintervals/superintervals, thus generalizing previous results in the literature [3] and basically disproving a conjecture by Lodaya [6].…”
Section: Introductionmentioning
confidence: 92%
“…While the satisfiability problem for spatial modal logics with projection modalities turns out to be highly undecidable [7,9], we prove that Cone Logic enjoys a decidable satisfiability problem (in fact, PSPACE-complete) by taking advantage of a suitable filtration technique. We also show that Cone Logic subsumes interesting interval temporal logics such as the temporal logic of subintervals/superintervals, thus generalizing previous results in the literature [3] and basically disproving a conjecture by Lodaya [6].…”
Section: Introductionmentioning
confidence: 92%
“…As pointed out in [17], one of the possible measures of the expressive power of a directional-based spatial logic for rectangles is the comparison with Rectangle Algebra (RA) [12]. In RA, one considers a finite set of objects (rectangles) O 1 , .…”
Section: Expressive Power Of Dacmentioning
confidence: 99%
“…In general, given an algebraic constraint network, the main problem is to establish whether or not the network is consistent, that is, if all constraints can be jointly satisfied. In [17], it has been shown that SpPNL is powerful enough to express and to check the consistency of an RA-constraint network. In [19], the authors show that the same can be done with its decidable fragment WSpPNL.…”
Section: Expressive Power Of Dacmentioning
confidence: 99%
See 1 more Smart Citation
“…Some spatial logics, which can encode directions, are undecidable, e.g. the compass logic [Marx and Reynolds, 1999] and SpPNL [Morales et al, 2007]. The satisfiability problem of some spatial logics (e.g.…”
Section: Introductionmentioning
confidence: 99%